Larangan Ingkar Tanggung Jawab dalam QS. al-Ṣāffāt 139-148 Studi Hermeneutika Abdullah Saeed Atas Kisah Nabi Yūnus - Althaf Husein Muzakky (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
Responsibility is a substantial thing. Almost at least a large part of welfare is determined by implementing responsibilities. This article explores the story of the Prophet Yūnus in the Qur'an related to the Responsibility Statement. Through the Abdullah Saeed hermeneutics method this research aims to reveal the significance and value of the hierarchy in the story of the Prophet Yūnus contained in the QS. al-Ṣāffāt verses 139-148. The results of this study reveal that in the story of the prophet Yūnus has significance in the form of tasliyyah (entertainment) specifically for the prophet Muhammad's task and the da'wah of Islam in general. The significance of the story of the prophet Yūnus has three urgencies namely Not running away from the responsibilities that have been mandated, not abusing authority, and being patient and polite in Da'wah Facing the people.